Analisis Pengambilan Keputusan Pembelian Kosmetik Berlabel Halal MUI pada Generasi Millenial - Badriyyatus Sholikhah; Resfa Fitri; Yekti Mahanani (Al Maal: Journal of Islamic Economics and Banking, 2021)
Millennial generation is consumption oriented generation. They are smart, trendsetter, and brand conscious. One of the products which is consumed by millennial generation is cosmetic products. Consumption of global halal cosmetics had a significant increased by 4.9 percent in 2018 or reached USD 64 billion where Indonesia is the second country as a global halal cosmetics consumer with a total expenditure of USD 4 billion. This study aims to analyze the factors influencing millennial generation in their decision to purchase halal MUI certified cosmetics. This research conducted in East Jakarta, Indonesia with 100 respondents. The method used in this research is logistic regression analysis. The result shows that halal knowledge, halal awareness, and brand image had a significant positive influence on the decision to purchase cosmetics labeled Halal MUI by the millennial generation of East Jakarta. It is expected that domestic cosmetic manufacturers will immediately certify and labeling halal MUI as a form of consumer protection. This is also important in increasing domestic cosmetic production, and to make Indonesia becomes manufacturer of halal cosmetic products.